2016
DOI: 10.17531/ein.2016.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Cycle life prediction of lithium-ion cells under complex temperature profiles

Abstract: These studies mentioned above, however, are mainly conducted based on the cycle life tests under one or more deterministic temperature levels, in which the high-precision temperature chamber and rigid data acquisition methods are required. Unlike the laboratory testing condition, cells in the field-use condition are usually run under complex temperature profiles. Previous researches indicate that the capacity fading process of Lithium-ion cells is significantly influenced by temperature [5,7,10]. In [10], capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The tests were conducted under conditions of accelerated aging -at discharge currents I d = 1C and I d = 2C and at temperatures T a = 25°C and T a = 40°C. Effect of fluctuating ambient temperature on the capacity loss process of LiFePO 4 cell was investigated and modeled in the paper [33]. In paper [35] Dessaint et al implemented two multi-parametric models which allow for the determination of the maximum number of cycles which may be carried out by LiNiMnCoO 2 and LiFePO 4 cells, depending on the actual cycling parameters (I d, I ch , DoD, T a ).…”
Section: Related Papersmentioning
confidence: 99%
“…The tests were conducted under conditions of accelerated aging -at discharge currents I d = 1C and I d = 2C and at temperatures T a = 25°C and T a = 40°C. Effect of fluctuating ambient temperature on the capacity loss process of LiFePO 4 cell was investigated and modeled in the paper [33]. In paper [35] Dessaint et al implemented two multi-parametric models which allow for the determination of the maximum number of cycles which may be carried out by LiNiMnCoO 2 and LiFePO 4 cells, depending on the actual cycling parameters (I d, I ch , DoD, T a ).…”
Section: Related Papersmentioning
confidence: 99%
“…Therefore, in some works, numerous simplifications of the models were made, for example, [16] reported that during SOH modeling it is mainly the amount of electric charge exchanged by the cell that must be taken into account. In [17,18], models of cell SOH were proposed for cells operating at a constant temperature or under a constant load. Many sources suggest taking into account different operating parameters, but assume only their averaged values during the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Although manufacturers of battery recommend maintaining the temperature in a range of 25ºC to 30ºC for extending battery life [7], temperature deviates from the range due to instantaneous battery activity of charging and discharging. In [8], it is shown that maximum battery cell temperature increases with the change of charge and discharge current where the ambient temperature is below the cell temperature. According to [9] - [11], temperature rise accelerates the battery life degradation.…”
Section: Introductionmentioning
confidence: 99%